ANTIBACTERIAL POTENTIAL ETHANOL EXTRACT OF KAYU RACUN LEAF (Rhinacanthus nasutus) AGAINST Staphylococcus aureus AND METHICILLIN RESISTANT Staphylococcus aureus - Febria, Fuji Astuti; Rahmadeni, Yossi; Bachtiar, Amri (Jurnal Pendidikan Matematika dan IPA, 2021)
The excessive use of antibiotics in the treatment of infections or diseases caused by Staphylococcus aureus is the main cause of antibiotic resistance. Methicillin-resistant S. aureus (MRSA) strains are a serious problem because of their wide distribution in the clinical environment and the living community, so it is necessary to search for antibacterial sources from natural products and traditional medicines such as Kayu racun leaves (Rhinacanthus nasutus). Information regarding the content of the active ingredient and the antibacterial potential of the ethanol extract of Kayu racun leaves is still limited. This study aims to test the phytochemical and antibacterial activity of the ethanol extract of Kayu racun leaves against S. aureus and MRSA bacteria by invitro. The research used an experimental method and was divided into two stages, namely; Phytochemical test of the ethanol extract of Kayu racun leaves using the Thin Layer Chromatography (TLC) method and the antibacterial activity test of the ethanol extract of Kayu racun leaves against S. aureus and MRSA using the paper disc diffusion method. Based on the research results, it can be concluded that the ethanol extract of Kayu racun leaves contains alkaloids, phenols, and flavonoids. The best antibacterial activity was found at a concentration of 100 mg/ml with an inhibition zone diameter of 26.20 mm against S. aureus and 17.90 mm against MRSA.